Reduplication In Nurwina Sari’s Novel 3726 MDPL - Yuli Charina Br Ginting Manik; Melany Renita Manullang; Rosa Darliana Br Tarigan; Geby Amanda Sihombing; Esron Ambarita (Jurnal Dieksis ID, 2026)
This study is urgent because analyzing reduplication in Nurwina Sari’s novel 3726 MDPL reveals how morphological patterns contribute to meaning, style, and emotional expression in contemporary Indonesian literary discourse. Reduplication is one of the most productive morphological processes in Indonesian and plays a significant role in conveying grammatical as well as semantic meanings. This study aims to analyze the forms and functions of reduplication found in the novel 3726 MDPL. The research focuses on identifying the types of reduplication and explaining their semantic contributions within the narrative context. This study employs a qualitative descriptive method, using textual data taken from the novel as the primary source. The data were collected through careful reading and note-taking techniques, and analyzed based on morphological theories proposed by linguists such as Ramlan, Chaer, Katamba, and Aronoff. To ensure data validity, the identified reduplicated forms were repeatedly cross-checked through multiple readings and verified using consistent classification criteria grounded in established morphological theories. The findings reveal that full reduplication is the most dominant type found in the novel, followed by partial and affixed reduplication. Semantically, reduplication functions to express plurality, intensity, repetition, continuity, and emotional emphasis. The results of this study are compared with previous studies on reduplication, particularly those conducted by Ambarita (2023) and Ambarita and Sembiring (2025). This research contributes to morphological studies by highlighting the use of reduplication in modern Indonesian literary texts and demonstrating its stylistic and semantic significance.